Energy-Based Evaluation of Brittleness in Moderately Weathered Rocks Under Triaxial Compression - Lianghong Lv; Enze Yin; Xiaoyu Liu; Ke Wu (Civil Engineering Journal, 2026)
Moderately weathered rock masses are widely encountered in deep and long tunnels, where excavation-induced unloading–reloading and stress concentration strongly affect failure behavior, stability, and support design. To clarify their brittleness from an energy perspective, this study develops a unified three-dimensional numerical framework for the triaxial compression analysis of five typical moderately weathered rocks, namely granite, basalt, limestone, shale, and sandstone, with the Jinmen Tunnel of the Longchuan–Huaiji Expressway as the engineering background. A coupled damage–plasticity constitutive model is adopted, and its parameters are calibrated using laboratory triaxial test data. Model reliability is verified by the close agreement between simulated and measured stress–strain curves and failure patterns of moderately weathered granite. The external work is decomposed into total, elastic, and dissipated energy densities, and a normalized dissipated energy is introduced to describe damage evolution. Results show that the energy evolution is strongly lithology-dependent: granite and shale exhibit a clear transition to post-peak dissipation-dominated behavior, whereas basalt, limestone, and sandstone remain mainly controlled by elastic energy. Increasing confining pressure from 5 to 10 MPa expands the dissipation zone and reduces the energy-density brittleness index BED, indicating a ductilizing effect. The novelty lies in the unified energy-based framework, the normalized dissipated energy, and the newly proposed BED for brittleness evaluation.